(3CWYeI GdeQVis - (3eMeO Hf YHO Gddg GdHZOGOj, TeS GdOjf GdJSJQjs ((3OjGQ GdQhe s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd GdCeGe GdYdGeI GdfGHZI fLjH GdOjf HajeI GdeSGjd CTGQ Ydi Cf GdhGLH Ydi cd Pi s
(3BNQgG (B:s
(3CNQL GdUaQGA hjfHZi Cf jchf GdeYJeO efg GdMdh ebGdGJg CHdZ ai JdWja GdMQGQI s
(3fSNI KGfjIs
(3hcJH YdjgG CfgG ef JCdja (B: (3fLjH GdOjf eMeO Hf Ydi GdSeQbfOi hgh hbes
(3YHGQI Yf eLehYI ai GdWH JTJed CWYeI GdeQNi hGdCOhjI GdeaQOIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs